What influences BSW students' attitudes towards cross-border marriage immigrants? The Taiwanese case of female marriage immigrants from China. Issue 3 (3rd July 2019) - Lee, Shou-Lu
ABSTRACT: This study enriches the literature on social work education and attitudes towards immigrants by showing that students in bachelor's social work programmes generally have friendly attitudes towards Chinese female marriage immigrants in Taiwan. College-level multicultural education does not always improve students' attitudes; improvement depends on students' performance in the courses. Direct contact is the most effective form of intergroup contact in terms of improving students' attitudes. Ethnicity matters in shaping students' attitudes: Minnanren students have significantly less friendly attitudes towards these immigrants. The findings have implications for social work educators in terms of curriculum design and marriage migration policy advocacy.